Efficient in vitro Planting Materiel Production of Ginger (Zingiber officinale roscoe) - Cacaï, Gilles Habib Todjro; Kango, Florentin Danton; Ahanhanzo, Corneille; Houédjissin, Serge Sètondji; Kouke, Jaures Riwan Uriel; Houngue, Jerome Anani (Discoveries in Agriculture and Food Sciences, 2024)
Conventional seed production techniques in Zingiber officinale roscoe are not appropriate to solve problems relative to the anthropogenic pressure, the biotic constraints, and low-rate multiplication by asexual mode. This study aimed to evaluate the in vitro culture conditions for explants disinfection, plantlets proliferation/rooting, and plant acclimatization of ginger. Buds, after treatment following various concentrations of mercuric chloride and immersion durations are cultured on the basic medium of Murashige and Skoog (MS) supplemented with NAA and Cytokinins (BAP / Kinetin / Zeatin) for six weeks of culture. The results indicated a highly significant (P ˂ 0.001) and very highly significant (P ˂ 0.0001) difference between disinfection treatments, proliferation, rooting, and organogenesis culture media. Treatments with HgCl2 (0.05%) for 5 min and 10 min on the one hand and with HgCl2 (0.1%) for 10 min of immersion on the other hand were indicated for the survival explants. The culture medium with plant growth regulator combination 0.5mg/l (NAA) + 4mg/l(BAP) was more favorable for shoots proliferation (6.27±0.4), leaves number (9.53±1.3) while the medium at 0.5 mg/l of NAA + 4 mg/l of Kinetin (7.5 cm) better influenced the growth of the shoots. As for rhizogenesis, 0.5 mg/l of NAA was more favorable for the length of the roots (7cm), and the number of roots formed (20.2). Acclimatization was more successful by weaning in growing room conditions with a survival rate of 70% after 4 weeks. This study will better impact the large-scale production of ginger plantlets and guide research on the production of its secondary metabolites.